The effect of metal loading over Ni/Î³-Al2O3 and Mo/Î³-Al2O3 catalysts on reaction routes of hydrodeoxygenation of rubber seed oil for green diesel production - Ameen, M. (Elsevier B.V., 2020)
Hydrodeoxygenation (HDO) of vegetable oil is one of the promising key processes designed for a possible convenient method for automotive clean fuel production. The HDO of rubber seed oil into diesel range hydrocarbon over non-sulphided monometallic (Ni/Î³-Al2O3 and Mo/Î³-Al2O3) catalysts were investigated. The catalysts were synthesized via conventional wet impregnation method using 3 wt., 12 wt. and 15 wt. Ni and Mo loading over Î³-Al2O3 support, to examine the influence of metal loading on catalytic activity, coke deposition, and reaction routes. The synthesized catalysts were subjected to characterization techniques including XRD, FESEM coupled with EDX, BET, TEM, TGA, ICP-OES and H2TPR. All the catalysts were tested for HDO reaction at 623.15 K, 3.5 MPa, H2/oil of 1000 N (cm3/cm3) with WHSV = 1 hâ1 in a continuous flow fixed bed tubular reactor. The hydrocarbon products were analyzed using gas chromatography, and intermediates were identified using GCâMS. The Ni supported catalysts showed comparatively higher surface area, small particle size, homogeneous dispersion of particles, higher crystallinity and lower reduction temperature, low coke deposition. Proposed reaction mechanism suggests the decarboxylation (DCO2) reaction occurred mainly over Ni supported catalysts. Whereas, higher Ni loading reduced the extent of decarboxylation (DCO2) reaction. Additionally, Mo supported catalysts allowed the deoxygenation reaction to occur and higher Mo loading enhanced the extent of hydrodeoxygenation (HDO). The triglycerides conversion for all the catalysts was 99.9. The catalysts with higher metal loading showed overall higher catalytic activity for hydrodeoxygenation of RSO. 15 wt. Ni loading produced higher hydrocarbon yield (55.1 wt.) whereas, 15 wt. Mo loading produced up to 61.7 wt.. Mo comparatively produced high amount of C16 (15.7 wt.), and C18 (30.7 wt.) hydrocarbons. Whereas, Ni produced mainly C15 (20.9 wt.) and C17 (20.3 wt.) hydrocarbons. Significant findings were observed on hydrocarbon yield, intermediates, and amount of coke formation. Mo supported catalysts shows significant HDO activity with less concentration of oxygenated component in the mixture. Besides Mo supported catalysts exhibit the high amount of coke deposition compared to Ni supported catalysts. Â© 2019 Elsevier B.V.